Efektivitas Program Sistem Layanan Online Dinas Kependudukan Dan Pencatatan Sipil Kota Depok Bersih Mudah Lancar (Silondo Bermula) Pada Pelayanan Pencetakan E-KTP - Dwi Cahyo Nugroho; Aryo Santiko (Jurnal Ilmu Administrasi Publik, 2023)
KTP Printing Services. Through Silondo Bermula, the people of Depok City effectively printed e- KTP. This is since services can only be performed via WhatsApp. However, the results of observations showed that some residents complained that the online form provided for uploading requirements could not be accessed and that there were residents who complained that they had to wait more than 7 days to print the e-KTP, while the SOP for printing the e-KTP only took 4 days. The type of research used is a type of qualitative research with a descriptive approach intended to solve research problems by describing, interpreting, and describing inductively (from general to specific) conditions according to reality in the field through processes and meanings based on a subjective perspective. The implementation of the Silondo Bermula program for printing e-KTP went well, the socialization of the Silondo Bermula service was quite good, the achievements of the Silondo Bermula program were good, the monitoring process was very good, and the accuracy of the Silondo Bermula program's target for e-KTP printing services was very effective. Program socialization in terms of outreach to the public about e-KTP printing services in the Silondo Bermula program has not been effectively implemented. The purpose of the e-KTP printing service in the Silondo Bermula  program is considered to have been effective in achieving the expected goals. Program monitoring in the Silondo Bermula program is carried out optimally. The results obtained are effective.